Hispanic Male Cancer Survivors’ Coping Strategies - Sommariva, Silvia; Vázquez-Otero, Coralia; Medina-Ramirez, Patricia; Aguado Loi, Claudia; Fross, Marshara; Dias, Emanuelle; Martinez Tyson, Dinorah (Hispanic journal of behavioral sciences, 2019)
Cancer survivors manage their new status using a multitude of coping mechanisms. Coping strategies vary by individual, but are also socioculturally mediated. Scarce evidence on coping strategies adopted by Hispanic male cancer survivors (HMCS) is available to date. The purpose of this study was to explore the reaction to diagnosis and subsequent coping strategies employed by HMCS. Data were gathered through focus groups (n = 18), cognitive interviews (n = 12), and phone interviews (n = 84). Coping strategies included positive attitudes, humor, optimism and social support, use of home remedies, lifestyle changes, and faith. Findings are consistent with research on non-cancer-related coping showing that HMCS use active coping strategies, such as religion and support from family and friends. The analysis of existing strategies and needs points to the need to develop evidence-based psychosocial services that build on strengths and coping behaviors already employed by HMCS.